Outcome of Malaria Associated Renal Failure (MARF) Treated with Acute Peritoneal Dialysis (Journal of Chittagong Medical College Teachers' Association, 2010)
Keywords: faciparum malaria; intermittent peritoneal dialysis; multi-organ failureDOI: 10.3329/jcmcta.v20i2.5620Journal of Chittagong Medical College Teachers' Association 2009: 20(2):16-18